Effect of organic and integrated nutrient management practices on soil phosphorus fractions and total phosphorus in basmati-wheat sequence - SHARMA, SEEMA; SAROA, G. S. (Journal of Soil and Water Conservation, 2020)
Effect of organic and integrated nutrient management practices on phosphorus fractions and total phosphorus (P) in basmati-wheat sequence were investigated in a long term fertilizer experiment which is in progress since rabi 2006-07, at Research Farm of Department of Soil Science, Punjab Agricultural University Ludhiana. All the phosphorus fractions (Sa-P, Fe-P, Al-P and Ca-P) were lowest in control and highest in INM2 treatment. Total P also followed similar trend. Ca-P was dominant fraction constituting between 29.1% and 58.05% of total P and representing an average of 49.2% of total P. Sa-P was less abundant P fraction in soils, constituting between 0.72% and 2.88% of the total P. Fe-P and Al-P constitutes between 5.56% and 13.8% and between 13.2% and 18.5 % fraction of total P. Correlation coefficients of soil P fractions with basmati yield and nutrient uptake were worked out which revealed that grain yield was strongly influenced by Sa-P, Al-P and Ca-P. Ca-P and Al-P were the dominant P fractions contributing towards P nutrition to basmati crop. Correlation coefficients of soil P fractions with wheat yield and nutrient uptake reveals that yield parameters and nutrient uptake significantly correlated with all soil P fractions.